Effects of potassium treatment on SnO2 electron transport layers for improvements of perovskite solar cells. (February 2022) - Kim, SeongYeon; Zhang, Fei; Tong, Jinhui; Chen, Xihan; Enkhbayar, Enkhjargal; Zhu, Kai; Kim, JunHo
Graphical abstract: Highlights: Effects of KCl treatment on SnO2 ETL and perovskite absorber were investigated. KCl treatment modified conduction band minimum and Fermi energy so as to improve band alignment between ETL and perovskite absorber. By the KCl treatment, K + ion diffused into absorber and passivated defects both at perovskite/ETL interface and in bulk perovskite. Admittance spectroscopy firstly showed direct evidence of the defect passivation via the diffused K + ion. Due to better band alignment and defect passivation, J-V hysteresis was diminished in the KCl-treated cell. Abstract: SnO2 has been studied intensively as an electron transport layer (ETL) for highly efficient metal halide perovskite solar cells. However, SnO2 ETL frequently exhibits defect-related issues associated with the bulk SnO2 and the perovskite/SnO2 interface, and to passivate the defect states potassium ion has been used. In order to investigate the passivation effect of potassium ion, we carried out KCl treatment on the solution-processed SnO2 ETL. It was found that KCl-treatment shifted up conduction band maximum and Fermi energy of SnO2, and reduced the band gap of perovskite absorber by K + diffusion, which resulted in a better conduction band alignment at perovskite/SnO2 . Admittance spectroscopy revealed that diffused K + ions can passivate defects of the perovskite absorber layer. With the improvement of band alignment and defect passivation via the KCl treatment, the J-V hysteresis was almost eliminated and power conversion efficiency was much enhanced with improved open-circuit voltage and fill factor.